Theoretical model for double-skinned concrete-filledsteel-tubular columns with external confinement - Dong, Chun Xiao; Ho, Johnny Ching Ming (Journal of Civil Engineering and Management, 2015)
Recent advances in the production of super-fine cement and filler technology has made the production of high-strength concrete (HSC) of 120 MPa practicable in the industry. Nonetheless, the application of such HSC in real construction is still limited. One of the reasons that inhibits the use of HSC is the brittleness, which causes HSC structures to fail explosively if the concrete confinement is not adequate. The traditional method of installing transverse steel as confinement is not feasible in HSC structures, as the steel will be too congested to ensure proper concrete placing. To overcome the problem, double-skinned high-strength concrete-filled-steel-tubular (HSCFST) columns has been advocated, which could provide large, continuous and uniform confinement to HSC. However, a major shortcoming of the double-skinned HSCFST columns is the imperfect interface bonding that occurs at the elastic stage that reduces the elastic strength and stiffness of columns. To improve the situation, the authors have verified previously that using external steel rings on the outer steel tube can successfully restrict the dilation of HSCFST columns and thus restore an intact interface bonding condition. As a continued study, the authors will in this paper develop a theoretical model for predicting the uni-axial load-carrying capacity of doubled-skinned HSCFST columns.